Dog Man : Lord of the Fleas - Book 5 Lord of the fleas - Pilkey, Dav 1966-; Garibaldi, Jose (New York, NY Graphix, an imprint of Scholastic, 2018)
When a new bunch of baddies bust up the town, Dog Man is called into action -- and this time he isn't alone. With a cute kitten and a remarkable robot by his side, our heroes must save the day by joining forces with an unlikely ally: Petey, the World's Most Evil Cat. But can the villainous Petey avoid vengeance and venture into virtue?
Keywords: Dogs -- Comic books, strips, etc; Police -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Robots -- Comic books, strips, etc; Comic books, strips, etc -- United States; Dogs -- Fiction; Police -- Fiction; Cats -- Fiction; Robots -- Fiction; Humorous Stories; Action and adventure comics; Humorous comics; Graphic novels; Comics (Graphic works)